PENGEMBANGAN E-LKPD MENGGUNAKAN APLIKASI WIZER.ME PADA MATERI KONDISI PEREKONOMIAN DI DAERAHKU - Febriyanti Bahari, Anggita; Rostikawati, Teti; Ade Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to develop E-LKPD using an application Wizer. me about the economic conditions in my area. Research methodology used Research and Development ADDIE development model (Analysis, Design, Development, Implementation, evaluation). The purpose of this research was carried out at SDN Ciawi 03 Bogor Regency in the even semester of the 2023/2024 school year. In this study, validation tests were carried out on E-LKPD products by media, language, and material experts. The results of validation by media experts obtained 91% with very feasible criteria, linguists obtained 100% with very feasible criteria, and by material experts 76% with feasible criteria. The results of the student response questionnaire were 93% in the very good category and the average score of N-Gain Learning Outcomes was 0.74 in the high category. The results show that E-LKPD using the Wizer. My application is very suitable for the learning process and can improve student learning outcomes.